ON THE ISSUE OF THE COLLAPSE OF THE SOVIET EMPIRE - Martirosyan, S. (Main Issues Of Pedagogy And Psychology, 2013)
The author of the article argues that the M. Gorbachev Reconstruction (Perestroyka) had deliberately been designed to cause the collapse of the Soviet Union, to drag the country in the world economy and lay a foundation to establish a “New World Order”. Meanwhile, the author demonstrates how the process of collapse was kept secretly, and the role of foreign factors contributed to that collapse.